Non-Directive Teaching Model as a Humanistic Approach in Islamic Religious Education at SD Negeri 16 Koto Baru - Faradila, Hanesty (UIN Siber Syekh Nurjati Cirebon, 2025)
Teachers as the spearhead of education with all the competencies they have are obliged to educate, teach, foster, and direct students to achieve educational goals that educate the nation's life. The purpose of this research is to find out the application of non-directive teaching models as a humanistic approach that is able to please and understand the needs of students in the learning process at school. Therefore, every teacher must have good knowledge related to learning models that suit the needs of students. Because the characteristics of each student in learning are diverse. This research uses qualitative methods with case studies, through interviews, observations and documentation. The results of this study show that the teacher's role in the non-directive learning model is as a facilitator and collaborator in the process of exploring students' identities and solving problems. This is what is meant by non-patronizing or non-directive. The main key to success in applying this model is the partnership between teachers and students. Thus, the application of this model as a humanistic approach in Islamic Religious Education at SD Negeri 16 Koto Baru is considered effective in developing students' character and spirituality, and it is recommended that its implementation be supported through teacher training programs, improved learning media facilities, and active involvement of parents and communities to support the educational process.Keywords:Non-Directive Model, Humanistic, Islamic Education